2020
DOI: 10.1038/s41598-020-59070-8
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of the head proteome of nurse honeybees (Apis mellifera) exposed to field-relevant doses of pesticides

Abstract: Understanding the effect of pesticides on the survival of honeybee colonies is important because these pollinators are reportedly declining globally. In the present study, we examined the changes in the head proteome of nurse honeybees exposed to individual and combined pesticides (the fungicide pyraclostrobin and the insecticide fipronil) at field-relevant doses (850 and 2.5 ppb, respectively). The head proteomes of bees exposed to pesticides were compared with those of bees that were not exposed, and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 84 publications
2
13
0
7
Order By: Relevance
“…These genes are considered homologous to small hsps in D. melanogaster (Chang & Geib, 2018;Kyriakis et al, 1994). They were also found in Aedes aegypti (Runtuwene et al, 2020) and A. mellifera (Zaluski et al, 2020). In this study, we found 8 different variants in T2 versus T3 and T2 versus T1 (Table 4).…”
Section: Discussionsupporting
confidence: 51%
“…These genes are considered homologous to small hsps in D. melanogaster (Chang & Geib, 2018;Kyriakis et al, 1994). They were also found in Aedes aegypti (Runtuwene et al, 2020) and A. mellifera (Zaluski et al, 2020). In this study, we found 8 different variants in T2 versus T3 and T2 versus T1 (Table 4).…”
Section: Discussionsupporting
confidence: 51%
“…Residues of agrochemicals detected in royal jelly are typically much lower than levels in worker diet (Johnson and Percel 2013;DeGrandi-Hoffman et al 2015;Böhme et al 2018), suggesting that nurse bees are capable of efficiently metabolizing agrochemicals in a manner that protects young larvae and queens from exposure to high levels of many agrochemicals. However, even pesticides that do not persist at detectable levels in diet may pose risks to developing brood and reproductive castes through persistence in wax (Wu et al 2011) or by altering the physiology and immune function of their worker caretakers (DeGrandi-Hoffman et al 2015;Zaluski et al 2020). As reviewed here, field-and semi-field-level experiments have demonstrated that feeding colonies IGDs can result in brood loss, suggesting that they are not always adequately protected from IGD exposure by the "shared stomach" at the doses studied.…”
Section: Effects Of Igds On Coloniesmentioning
confidence: 93%
“…O volume normalizado (%V) de cada spot proteico obtido nos géis do grupo controle foi utilizado para determinar diferenças significativas entre spots proteicos dos grupos expostos aos agrotóxicos por meio de análise de variância (ANOVA); o nível de significância adotado foi de p < 0,05. Posteriormente, foi realizada identificação de proteínas em spots que apresentaram redução de expressão por ESI-MS/MS (Electrospray Ionisation Tandem Mass Spectrometry) Zaluski et al, 2020).…”
Section: Methodsunclassified
“…As abelhas melíferas apresentam grande capacidade de forrageamento, o que torna esses insetos mais susceptíveis a coleta de recursos alimentares contaminados com agrotóxicos. A detecção de agrotóxicos sistêmicos em colônias de A. mellifera tem se tornado cada vez mais comum (Colwell et al, 2017;Zaluski et al, 2020) gerando impactos negativos para a manutenção das colônias. Destaca-se que para a secreção de geleia real, as abelhas nutrizes consomem grande quantidade de pólen, se tornando altamente susceptíveis a exposição de agrotóxicos presentes nesse recurso (Rortais et al, 2005;Colwell et al, 2017).…”
Section: Introductionunclassified